Islamic Religious Education Learning Innovation Using the Course Review Horay Model - Adel, Samiullah; Nurhayati, Nurhayati; Endra, Endra; Satrial, Ardi; Nurainiah, Nurainiah (International Journal of Islamic Teaching and Learning, 2024)
Lack of it Innovation in Islamic Religious Education learning also has an impact on students' low learning scores. Another phenomenon is that teachers do not give students enough opportunities to be active, and rarely give appreciation. For this reason, this research aims to describe the analysis of the implementation of the course review horay model in improving student learning outcomes in Islamic Religious Education learning. This research was conducted in the form of classroom action research at an elementary school in Indonesia. Data was collected using observations and tests from Islamic Religious Education teachers and fourteen students. All data is processed using descriptive statistical analysis. This research found that the course review horay model can improve students' Islamic Religious Education learning outcomes from the first cycle to the second cycle. The use of this model in Islamic Religious Education learning is an innovation that can improve learning outcomes, activate students, and provide appreciation, especially in elementary schools.